Skills training by small and medium-sized enterprises: Innovative cases and the consortium approach in the Republic of Korea - Kye-woo Lee (Asian Development Bank Institute (ADBI), 2016)
This paper presents targeted government policies for promoting training in small and medium-sized enterprises (SMEs) to increase their contributions to economic development. It first discusses the role of SMEs in country development and the special challenges facing SMEs in developing human resources. It then surveys some innovative, targeted policies for promoting training by SMEs in Asia and Latin America. The paper elaborates on the objectives and achievements of a successful targeted SME training policy, the SME Training Consortiums Program in the Republic of Korea, as a best practice. This paper concludes with some cautionary remarks for developing countries seeking to adopt targeted SME training policies.
Keywords: O31; O32; O38; 330; SME training policies; SME Training Consortiums Program; training levy grants; Republic of Korea